SYMBOLIC INTERACTION IN THE COMMENTS OF RAINBOW FILMING FOOTAGE ON MARS INSTAGRAM @CUPLIKANFILM82 - Dhiya Prameswari; RR Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Social media has become a digital communication space that enables users to interact and construct meanings through various symbols, including emojis. This study aims to describe the forms of symbolic interaction and identify the meanings constructed by users in the comment section of the Instagram account @cuplikanfilm on a post featuring the behind-the-scenes process of the film Pelangi di mars. This research employed a qualitative approach using a descriptive qualitative method. Data were collected through observation, interviews, and documentation involving three informants and one expert triangulator. The findings indicate that symbolic interaction in the comment section is reflected through the use of emojis, informal language, and various forms of user engagement. Emojis are utilized as a means of expressing emotions, opinions, and appreciation toward the content presented. Furthermore, users interpret the film production content as a representation of visual quality, a source of expectations regarding the storyline, and a reflection of teamwork during the production process. User participation is not only demonstrated through commenting activities but also through reading comments and giving likes. The study concludes that meaning in digital interactions is formed through the interpretation of symbols influenced by users’ experiences, understanding, and social contexts.